EXPRESSIVE SPEECH ACTS FOUND IN LOVE AT FIRST SWIPE WEB SERIES - Ricca, Hery; Ambalegin, Ambalegin (CaLLs (Journal of Culture, Arts, Literature, and Linguistics), 2022)
This research aimed to find out the expressive speech acts uttered by the characters in Love at First Swipe web series. The data were taken from the related utterances found in the dialogues of the web series. The data were analyzed by using the expressive speech acts theorized by Searle (1979) & Ilie & Norrick (2018). This research applied the observational method and non-participatory technique by Sudaryanto (2015) for collecting the data. This research also applied the pragmatics equalizing method to analyze the data. As the results, there were 15 utterances of expressive speech acts found in the Love at First Swipe web series. However, there were only 2 types of expressive act not found in the utterances, they were deploring and condoling. The other expressive speech act types were found with 3 data of thanking, 2 data of apologizing, 1 data of congratulating, 8 data of complimenting, and 1 data of welcoming. Thus, the most common type of expressive speech act found in the Love at First Swipe web series was complimenting.